Chlorogenic acid supplementation ameliorates hyperuricemia, relieves renal inflammation, and modulates intestinal homeostasis. Issue 12 (21st May 2021) - Zhou, Xiaofei; Zhang, Bowei; Zhao, Xiuli; Lin, Yongxi; Wang, Jin; Wang, Xiaowen; Hu, Nan; Wang, Shuo
Abstract : Chlorogenic acid alleviates hyperuricemia by reducing uric acid synthesis in the liver and promoting uric acid excretion from kidneys and intestine, and it also relieves renal inflammation and regulates intestinal homeostasis. Abstract : Hyperuricemia (HUA) is induced by abnormal purine metabolism and elevated serum uric acid (UA) concentrations, and it is often accompanied by inflammatory responses and intestinal disorders. This study aims to assess the protective effects of chlorogenic acid (CGA) on HUA in mice. CGA or allopurinol was given to mice with HUA induced by hypoxanthine and potassium oxonate. CGA lowered the levels of UA, blood urea nitrogen (BUN), creatinine (CR), AST, and ALT; inhibited xanthine oxidase (XOD) activity; and downregulated the mRNA expression of UA secretory proteins in HUA mice. Moreover, CGA significantly reduced serum lipopolysaccharides (LPS) levels and the mRNA expression of interleukin (IL)-1β, tumor necrosis factor (TNF)-α, NOD-like receptor superfamily pyrin domain containing 3 (NLRP3), and caspase-1, and it inhibited the activation of the toll-like receptor 4/myeloid differentiation factor 88/nuclear factor kappa B (TLR4/MyD88/NF-κB) signaling pathway in the kidney, resulting in inflammation relief in HUA mice. In addition, CGA treatment increased the production of fecal short-chain fatty acids (SCFAs) in HUA mice. Additional investigations showed that CGA significantly lowered the mRNA expression of ileal IL-1β and IL-6, and it increased the mRNA expression of intestinal tight junction proteins (zonula occludens-1 (ZO-1) and occludin). Also, CGA increased the relative abundance of SCFA-producing bacteria, including Bacteroides, Prevotellaceae UGC-001, and Butyricimonas, and it reversed the purine metabolism and glutamate metabolism functions of gut microbiota. In conclusion, CGA may be a potential candidate for relieving the symptoms of HUA and regulating its associated inflammatory responses and intestinal homeostasis.